Discoursing disaster: power and actor of the Lapindo case in Indonesia - Novenanto, Anton (2016)
Focusing on a plethora of statements articulated by interrelated actors concerning the unnatural Lapindo mudflow in the region of Porong, East Java, Indonesia, this study explores how these actors have been enlivening and reviving the discourse of “disaster” following the hazard. The data of this study is gathered from a multifaceted research, especially the fieldwork within a disaster victim community that I conducted in 2009, 2010, 2012, and 2013 and a series of critical readings into media reportages, journal articles, and memories of the incident. Inspired by Michel Foucault’s discourse theory and analysis, this study aims to unravel power relations that have been generating the dynamic of the society by focusing on the “statements” stored and articulated by particular actors in various discursive fields. It is somewhat ethnography of conflicting and competing statements about what happened, the statements I collected during these periods of research have led me to a focal subject discussed in this dissertation, the relation of power and actor in the course of the disaster. I found that the mudflow has put particular actors in competing and therefore escalating power relations since each party has their own version of truth and been struggling to defend their claim and decline the others’ claim. Power relation between these actors has been escalation owing to public’s blame on the reckless drilling of an oil and natural gas company, Lapindo Brantas, has initiated the mudflow. It is very much predicted that the company is using its political and economic resources to limit or reduce its liability for causing such a calamity to the society and ecology and to such a purpose it has been colluded with the Indonesian government. In the course of the research, I found that much information has been manipulated by the collusion in order to steer public opinion from “industrial disaster” to “natural disaster” and as a result an unequal power relation between the collusion and mudflow victims has been characterizing the disaster since the beginning. To that end, throughout the chapters of this study I want to defend an argument saying that to some extent the mudflow and disaster resulted from it are indeed anthropogenic and what happen afterwards is just efforts of certain actors to prove or deny it. I am very much concerned with the issue of by problematizing of natural disaster claim over the mudflow and relating it with the notion of power has made me another actor of the disaster.